Cultural Norms, Masculinity, and System Design in Men’s Healthcare Avoidance in Cameroon - Paul Saah; Delphine Fri Chifor; Gisele Mah (Journal of Healthcare and Biomedical Science, 2025)
Men in Cameroon routinely underutilize formal healthcare services, causing a delay in diagnoses, poor health outcomes, and higher rates of death. This study intends to explore the interactions of cultural norms, constructions of masculinity, and structural design attributes on how they affect men’s avoidance of healthcare in Cameroon and suggest context-specific strategies to address it. Based on the results of a systematic review of the 50 most relevant scholarly works, this study aims to provide a data-driven, evidence-based account of men’s healthcare avoidance in Cameroon, combining theoretical analysis and practical reflections to discover prevalent themes, reveal knowledge deficiencies, and highlight opportunities for developing more male-focused health policies and interventions. The findings of the study depict that men’s avoidance of healthcare in Cameroon is based on interrelated factors, such as cultural norms surrounding strength and self-reliance, structural disregard for male-specific needs, concern for being stigmatized or loss of status, and practical as well as symbolic salience of traditional medicine. The results recommend efforts to deliver gender-inclusive healthcare interventions in Cameroon that address communication disparities, establish male-friendly spaces, and incorporate culturally appropriate practices while framing masculinity as a major social determinant of health that can mitigate exclusion and ensure equitable access. The study builds on information available on men’s health in sub-Saharan Africa and adds to the existing literature by proposing a framework in which cultural norms, masculinity, and system designs converge to drive healthcare avoidance, new perspectives, and specific recommendations for enhancing healthcare delivery in Cameroon.